Mandailing Customary Marriage Law in terms of Law 16 of 2019 concerning amendments to Law No.1 of 1974 - Dewi Robiyanti; Zetria Erma; Ismayani Ismayani; Yusuf Hanafi Pasaribu; Nirwana Dewi Harahap (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The aims of this study is to find out Mandailing Customary Marriage Law in terms of Law 16 of 2019. This study used qualitative research. The result of this study shows that That the dowry is part of the marriage custom of the Mandailing tribe, but in practice it has experienced a shift in value. Both from the substantive meaning and in its application. This is indicated by the practice that distinguishes between the marriage dowry to fulfill the provisions of the marriage and the tuor to fulfill the customary provisions. 2. Dowry is a gift from a prospective husband to a prospective wife based on simplicity and convenience. Although the delivery is carried out in cash, there is still an opportunity for the prospective husband to postpone part of the agreed dowry amount. 3. In the marriage agreement, it is very possible that the dowry is included in the category of gifts that can be paid not only in cash. Thus, disputes regarding dowry can become the authority of the Religious Courts.